Research on control methods and technology for reduction of large-scale wind turbine blade vibration - Feihang Zhou; Jianxiang Yang; Ji Pang; Bo Wang (Energy Reports, 2023)
This paper is mainly devoted to the analysis and suppression of large-scale wind turbine blade vibration. Firstly, the mechanism of blade vibration including waved vibration and shimmy vibration is analyzed in detail and the mathematical model of blade vibration is established. Secondly, the influence of tower shadow effect and wind shear on blade flutter is discussed based on the established blade vibration model. In the end, for the suppression of blade vibration, some control schemes based on individual variable-pitch including blade damping control, LQG control, H∞ control and improved LQG control with optimal disturbance observer proposed in this paper are studied. At the same time, the specific processes of controllers design are given and these algorithms are effectively verified by simulations. The results show that the improved LQG control with optimal disturbance observer has the better suppression effect on blade vibration compared with other methods, which can provide a certain theoretical support to choose the control algorithm in reality.